Exploring the Futures of Finland's International Accessibility : A Horizon Scanning and Scenario Based approach - Salo, Petra (My University, 2026)
The aim of this thesis is to explore how futures studies methods can be used to aid transport system planning and impact assessment, specifically in the context of the Finnish Transport Infrastructure Agency’s Investment program. This thesis is focused on the uncertainties related to Finland’s international accessibility. In the context of this thesis, international accessibility refers to how transport connections and services support the mobility and transportation needs of people, businesses and public administration in other countries and vice versa. The thesis utilizes two main methods: horizon scanning, which was used to scan for different future change factors and scenario planning, which was used to create scenarios to aid strategic decision-making. For the creation of the scenarios, I utilized Peter Schwarzt’s scenario method from his book The Art of the Long View. During the horizon scanning, I scanned for uncertainties in the future of Finland’s international accessibility by the year 2040 and sorted the findings according to the PESTLE – categories: political, economic, social, technological, legal and environmental. The findings included factors such as the possibility of new fixed Western connections and the green transition. Based on the horizon scanning, a questionnaire was conducted where experts from The Finnish Traffic Infrastructure Agency and Traficom were asked to review the future signals based on their impact and uncertainty. The three most impactful and uncertain factors then formed the basis of the scenario logics of the scenarios introduced in section 7 of the thesis. For this thesis, four scenarios were produced: Finland as an island, Bridges to the West amidst a storm, Clear waters and the Western Horizon. The Finnish Traffic Infrastructure Agency’s investment program for the years 2025 – 2032 worked as the case study in this thesis. In practice this means that some of the projects were tested against the scenarios to see how compatible they are with the scenarios. For this I utilized a simple scale of low, moderate, high and very high. These projects had various reasons for being compatible with the scenarios, but generally the projects that aligned well supported Finland’s international accessibility either through improved connections to Norway or Sweden or were located by the Western Coast. The reason these projects were compatible with the scenarios is that the projects are not as affected by the conflict in the Baltic Sea in scenarios 1 and 2.

Tämän opinnäytetyön tavoitteena on tarkastella kuinka tulevaisuuden tutkimuksen menetelmillä voidaan tukea liikennejärjestelmäsuunnittelua ja vaikutusten arviointia erityisesti erityisesti Väyläviraston investointiohjelman kontekstissa. Opinnäytetyö keskittyy Suomen kansainvälisen saavutettavuuden tulevaisuuden epävarmuuksiin. Työn kaksi päämenetelmää ovat horizon scanning, jonka avulla etsitään erilaisia tulevaisuuden muutostekijöitä ja skenaariosuunnittelua, jota käytetään luomaan skenaarioita strategisen päätöksenteon tueksi. Opinnäytetyössä on käytetty Peter Schwartzin skenaariomenetelmää hänen teoksestaan The Art of the Long View. Horizon scanning - prosessissa, skannasin muutostekijöitä liittyen Suomen kansainväliseen saavutettavuuteen vuoteen 2040 mennessä ja lajittelin löydökset PESTLE - kategorioittain: poliittinen, taloudellinen, sosiaalinen, laillinen, teknologinen, laillinen ja ekologinen. Löydöksiin kuului muuttujia kuten uuden merenkurkun kiinteän yhteyden mahdollisuus ja vihreä siirtymä. Horizon scanning - prosessin pohjalta suoritin kyselyn, jossa Väyläviraston ja Traficomin asiantuntijat arvottivat muutostekijät niiden vaikutuksen ja epävarmuuden pohjalta. Kolme vaikuttavinta ja epävarminta tekijää olivat Itämeren kasvavat jännitteet, merenkurkun kiinteän yhteyden mahdollisuus sekä vaatimukset uusista läntisistä yhteyksistä. Neljä luotua skenaariota ovat: Suomi saarena, Sillat länteen myrskyjen keskellä, Kirkkaat vedet ja Läntinen horisontti. Väyläviraston investointiohjelma vuosille 2025–2032 toimi työni tapausesimerkkinä. Käytännössä tarkastelin siis, kuinka yhteensopivia hankkeet ovat skenaarioiden olosuhteiden kanssa skaalalla matala, kohtalainen, korkea ja erittäin korkea. Näillä hankkeilla oli useita syitä menestyä skenaarioissa, mutta yleisesti ottaen hyvin menestyneet hankkeet tukivat Suomen kansainvälistä saavutettavuutta joko parempien Norjan tai Ruotsin yhteyksien kautta tai sijaitsivat länsirannikolla. Syy näiden hankkeiden erityisen hyvään yhteensopivuuteen on se, että Itämeren konflikti ei vaikuta niihin yhtä paljon skenaarioissa 1 ja 2.
Keywords: horizon scanning; scenario planning; international accessibility; transport planning; toimintaympäristönanalyysi; skenaariot; kansainvälinen saavutettavuus; liikennejärjestelmäsuunnittelu